BEYOND THE PING-PONG TABLE: BUILDING AUTHENTIC EMPLOYEE ENGAGEMENT - Bangun Budi Raharjanti; Ramon Zamora; Lukmanul Hakim (RADJA PUBLIKA, 2026)
Based on an analysis of qualitative employee interview data, this study investigates the primary drivers of authentic workplace engagement beyond material compensation. The objective was to identify the non-transactional factors that foster sustained commitment and discretionary effort. The results revealed four interconnected themes: the primacy of meaningful work over perks; the critical role of managerial support in building psychological safety; the necessity of clear career trajectories for growth; and the profound impact of personalized, authentic recognition. The discussion indicates that perks and pay are merely foundational, while true engagement is cultivated through purpose, safety, growth, and feeling valued as a whole person. The conclusion underscores that engagement is a reciprocal relationship, where employees invest fully in organizations that demonstrably invest in their employees’ professional and personal value.